Türk kültür ve medeniyet tarihinde Fatih Külliyesi, 1 : cami, medreseler, türbeler, kütüphâne, dârü’l-kurrâ, tabhâne = The Fatih Complex, 1 : in the history of Turkish culture and civilization : mosque, madrasahs, tombs, library, darul kurra, guesthouse - Günüç, Fevzi. (İstanbul)
320 s.